A simplified extracorporeal photopheresis procedure based on single high-dose ultraviolet A light irradiation shows similar in vitro efficacy - Buchele, Vera; Hackstein, Holger (Transfusion, 2020)
Background: Extracorporeal photopheresis (ECP) is one of the most widely used and effective cell-based therapies for the treatment of T-cell–mediated diseases. The patients' white blood cells (WBCs) are collected by apheresis and exposed to the photosensitizer 8-methoxypsoralen (8-MOP) and ultraviolet A (UVA) light before retransfusion. The UVA/8-MOP combination has been in use in ECP for more than 4 decades; however, whether ECP can be simplified by UVA light irradiation only has never been analyzed. Study Design and Methods: Peripheral blood mononuclear cells were treated with classical ECP or different UVA light doses only (UVAonly). Treatment efficacy was investigated by apoptosis induction in WBC subsets, inhibition of T-cell proliferation, and the ability of monocytes to induce allogeneic T-cell expansion and to respond to lipopolysaccharide and interferon-γ stimulation in vitro. Results: High-dose UVAonly treatment (5 J/cm2) was as efficient as ECP to induce apoptosis within 48 hours. UVAonly treatment modulated the composition of the surviving cells by improving monocyte survival and promoting CD8+ T-cell apoptosis. Both ECP and UVAonly treatment inhibited anti-CD3/anti-CD28 triggered T-cell proliferation. Interestingly, whereas ECP-treated monocytes exhibited a markedly reduced capacity to respond to stimulation and to induce allogeneic T-cell proliferation, UVAonly treatment preserved monocyte functionality to some degree. Conclusions: High-dose UVAonly and standard ECP showed comparable efficacy in inducing apoptosis and inhibiting direct T-cell proliferation. Hence, UVAonly treatment can be a simplified alternative to ECP therapy. Furthermore, increased monocyte survival with partially preserved functionality after UVAonly treatment may provide a novel method for immunoregulation.
CRIS-Team Scopus Importer:2020-12-25
Keywords: apoptosis; extracorporeal photopheresis; UVA light

BATF-dependent IL-7RhiGM-CSF+ T cells control intestinal graft-versus-host disease - Ullrich, Evelyn; Abendroth, Benjamin; Rothamer, Johanna; Huber, Carina; Büttner-Herold, Maike; Buchele, Vera; Vogler, Tina; Longerich, Thomas; Zundler, Sebastian; Völkl, Simon; Beilhack, Andreas; Rose-John, Stefan; et al. (Journal of Clinical Investigation, 2018)
Acute graft-versus-host disease (GVHD) represents a severe, T cell-driven inflammatory complication following allogeneic hematopoietic cell transplantation (allo-HCT). GVHD often affects the intestine and is associated with a poor prognosis. Although frequently detectable, proinflammatory mechanisms exerted by intestinal tissue-infiltrating Th cell subsets remain to be fully elucidated. Here, we show that the Th17-defining transcription factor basic leucine zipper transcription factor ATF-like (BATF) was strongly regulated across human and mouse intestinal GVHD tissues. Studies in complete MHC-mismatched and minor histocompatibility-mismatched (miHA-mismatched) GVHD models revealed that BATF-expressing T cells were functionally indispensable for intestinal GVHD manifestation. Mechanistically, BATF controlled the formation of colon-infiltrating, IL-7 receptor-positive (IL-7R+), granulocyte-macrophage colony-stimulating factor-positive (GM-CSF+), donor T effector memory (Tem) cells. This T cell subset was sufficient to promote intestinal GVHD, while its occurrence was largely dependent on T cell-intrinsic BATF expression, required IL-7-IL-7R interaction, and was enhanced by GM-CSF. Thus, this study identifies BATF-dependent pathogenic GM-CSF+ effector T cells as critical promoters of intestinal inflammation in GVHD and hence putatively provides mechanistic insight into inflammatory processes previously assumed to be selectively Th17 drive
EVALuna2:25783

Human T cells loaded with superparamagnetic iron oxide nanoparticles retain antigen-specific TCR functionality. - Pfister, Felix; Dörrie, Jan; Schaft, Niels; Buchele, Vera; Unterweger, Harald; Carnell, Lucas R.; Schreier, Patrick; Stein, René; Kubánková, Markéta; Guck, Jochen; Hackstein, Holger; Alexiou, Christoph; et al. (Frontiers in Immunology, 2023)
BACKGROUND: Immunotherapy of cancer is an emerging field with the potential to improve long-term survival. Thus far, adoptive transfer of tumor-specific T cells represents an effective treatment option for tumors of the hematological system such as lymphoma, leukemia or myeloma. However, in solid tumors, treatment efficacy is low owing to the immunosuppressive microenvironment, on-target/off-tumor toxicity, limited extravasation out of the blood vessel, or ineffective trafficking of T cells into the tumor region. Superparamagnetic iron oxide nanoparticles (SPIONs) can make cells magnetically controllable for the site-specific enrichment. METHODS: In this study, we investigated the influence of SPION-loading on primary human T cells for the magnetically targeted adoptive T cell therapy. For this, we analyzed cellular mechanics and the T cell response after stimulation via an exogenous T cell receptor (TCR) specific for the melanoma antigen MelanA or the endogenous TCR specific for the cytomegalovirus antigen pp65 and compared them to T cells that had not received SPIONs. RESULTS: SPION-loading of human T cells showed no influence on cellular mechanics, therefore retaining their ability to deform to external pressure. Additionally, SPION-loading did not impair the T cell proliferation, expression of activation markers, cytokine secretion, and tumor cell killing after antigen-specific activation mediated by the TCR. CONCLUSION: In summary, we demonstrated that SPION-loading of T cells did not affect cellular mechanics or the functionality of the endogenous or an exogenous TCR, which allows future approaches using SPIONs for the magnetically enrichment of T cells in solid tumors.
EVALuna2:539766
Keywords: Adoptive T cell therapy; superparamagnetic iron oxide nanoparticles (SPIONs); antigen-specific T cell response; targeted immune therapy; cell deformability

Induction of Intestinal Graft-versus-host Disease and Its Mini-endoscopic Assessment in Live Mice - Buchele, Vera; Büttner-Herold, Maike; Vogler, Tina; Neurath, Markus; Hildner, Kai (Journal of Visualized Experiments, 2019)
Acute graft-versus-host disease (GvHD) represents the most severe complication that patients previously undergoing allogeneic hematopoietic stem cell transplantation (allo-HCT) face and is frequently associated with a poor clinical outcome. While, for instance, GvHD manifestations of the skin are usually responsive to established immune-suppressive therapies and are, hence, not taking a fatal course, the presence and the intensity of intestinal GvHD, especially of the mid-to-lower parts of the gut, strongly influence the outcome and overall survival of patients with acute GvHD. Therapeutic options are essentially limited to the classic immune-suppressive agents yielding only moderate disease-mitigating effects. Hence, detailed knowledge about the tissue-resident immune cascade, changes in the intestinal microbiota, and the stromal response prior, upon, and after intestinal GvHD onset are urgently needed to understand the events and mechanisms underlying its pathogenesis and to develop innovative therapeutic options. Murine models of GvHD are frequently employed to identify and functionally assess molecules and pathways putatively driving intestinal GvHD. However, means to specifically monitor and evaluate intestinal inflammation over time are essentially lacking since established scores to assess and grade acute GvHD are routinely comprised of various parameters which rather reflect systemic GvHD manifestations. The detailed evaluation of intestinal GvHD has been restricted to studies using euthanized mice, thereby essentially excluding longitudinal (i.e., kinetic) analyses of the colonic compartment under a given experimental condition (e.g., antibody-mediated blockade of a proinflammatory cytokine) in live mice (i.e., in vivo). The mini-endoscopic in situ assessment of the distal colon of alloHCT-treated mice described here allows a) a detailed macroscopic evaluation of different aspects of intestinal inflammation and b) the option to collect tissue samples for downstream analyses at various time points over the course of the observation period. Overall, the mini-endoscopic approach provides a major advance in preclinical noninvasive monitoring and assessment of intestinal GvHD.
CRIS-Team WoS Importer:2019-04-12

Intestinal graft-versus-host disease is driven by BATF-dependent IL-7R(hi)GM-CSF+ T cells - Ullrich, Evelyn; Abendroth, Benjamin; Rothamer, Johanna; Huber, Carina; Buettner-Herold, Maike; Kitowski, Vera; Vogler, Tina; Longerich, Thomas; Zundler, Sebastian; Völkl, Simon; Beilhack, Andreas; Rose-John, Stefan; et al. (2018)
EVALuna2:207769

Methionine sulfoxide reductases are essential for virulence of Salmonella typhimurium - Denkel, Luisa A.; Horst, Sarah A.; Rouf, Syed Fazle; Kitowski, Vera; Böhm, Oliver M.; Rhen, Mikael; Jäger, Timo; Bange, Franz Christoph (PLoS ONE, 2011)
Production of reactive oxygen species represents a fundamental innate defense against microbes in a diversity of host organisms. Oxidative stress, amongst others, converts peptidyl and free methionine to a mixture of methionine-S- (Met-S-SO) and methionine-R-sulfoxides (Met-R-SO). To cope with such oxidative damage, methionine sulfoxide reductases MsrA and MsrB are known to reduce MetSOs, the former being specific for the S-form and the latter being specific for the R-form. However, at present the role of methionine sulfoxide reductases in the pathogenesis of intracellular bacterial pathogens has not been fully detailed. Here we show that deletion of msrA in the facultative intracellular pathogen Salmonella (S.) enterica serovar Typhimurium increased susceptibility to exogenous H 2O 2, and reduced bacterial replication inside activated macrophages, and in mice. In contrast, a ΔmsrB mutant showed the wild type phenotype. Recombinant MsrA was active against free and peptidyl Met-S-SO, whereas recombinant MsrB was only weakly active and specific for peptidyl Met-R-SO. This raised the question of whether an additional Met-R-SO reductase could play a role in the oxidative stress response of S. Typhimurium. MsrC is a methionine sulfoxide reductase previously shown to be specific for free Met-R-SO in Escherichia (E.) coli. We tested a ΔmsrC single mutant and a ΔmsrBΔmsrC double mutant under various stress conditions, and found that MsrC is essential for survival of S. Typhimurium following exposure to H 2O 2, as well as for growth in macrophages, and in mice. Hence, this study demonstrates that all three methionine sulfoxide reductases, MsrA, MsrB and MsrC, facilitate growth of a canonical intracellular pathogen during infection. Interestingly MsrC is specific for the repair of free methionine sulfoxide, pointing to an important role of this pathway in the oxidative stress response of Salmonella Typhimurium. © 2011 Denkel et al.
Created from Fastlane, Scopus look-up

STAT3 Activation in Th17 and Th22 Cells Controls IL-22-Mediated Epithelial Host Defense during Infectious Colitis - Backert, Ingo; Koralov, Sergei B.; Wirtz, Stefan; Kitowski, Vera; Billmeier, Ulrike; Martini, Eva; Hofmann, Katharina; Hildner, Kai; Wittkopf, Nadine; Brecht, Katrin; Waldner, Maximilian; Rajewsky, Klaus; et al. (Journal of Immunology, 2014)
The Citrobacter rodentium model mimics the pathogenesis of infectious colitis and requires sequential contributions from different immune cell populations, including innate lymphoid cells (ILCs) and CD4(+) lymphocytes. In this study, we addressed the role of STAT3 activation in CD4(+) cells during host defense in mice against C. rodentium. In mice with defective STAT3 in CD4(+) cells (Stat3(?CD4)), the course of infection was unchanged during the innate lymphoid cell-dependent early phase, but significantly altered during the lymphocyte-dependent later phase. Stat3(?CD4) mice exhibited intestinal epithelial barrier defects, including downregulation of antimicrobial peptides, increased systemic distribution of bacteria, and prolonged reduction in the overall burden of C. rodentium infection. Immunomonitoring of lamina propria cells revealed loss of virtually all IL-22-producing CD4(+) lymphocytes, suggesting that STAT3 activation was required for IL-22 production not only in Th17 cells, but also in Th22 cells. Notably, the defective host defense against C. rodentium in Stat3(?CD4) mice could be fully restored by specific overexpression of IL-22 through a minicircle vector-based technology. Moreover, expression of a constitutive active STAT3 in CD4(+) cells shaped strong intestinal epithelial barrier function in vitro and in vivo through IL-22, and it promoted protection from enteropathogenic bacteria. Thus, our work indicates a critical role of STAT3 activation in Th17 and Th22 cells for control of the IL-22-mediated host defense, and strategies expanding STAT3-activated CD4(+) lymphocytes may be considered as future therapeutic options for improving intestinal barrier function in infectious coliti
EVALuna2:1843

Targeting Inflammatory T Helper Cells via Retinoic Acid-Related Orphan Receptor Gamma t Is Ineffective to Prevent Allo-Response-Driven Colitis - Buchele, Vera; Abendroth, Benjamin; Buettner-Herold, Maike; Vogler, Tina; Rothamer, Johanna; Ghimire, Sakhila; Ullrich, Evelyn; Holler, Ernst; Neurath, Markus; Hildner, Kai (Frontiers in Immunology, 2018)
Intestinal graft-versus-host disease (GvHD) is a life-threatening, inflammatory donor T cell-mediated complication of allogeneic hematopoietic stem cell transplantation (allo-HSCT). In the light of the reported efficacy of interleukin-23 (IL-23)-blockade to mitigate syngeneic intestinal inflammation in inflammatory bowel disease patients, targeting IL-23 and thereby interleukin-17a (IL-17a) producing T helper (Th17) cells as the T cell subset assumed to be mostly regulated by IL-23, has emerged as a putatively general concept to harness immune-mediated mucosal inflammation irrespective of the underlying trigger. However, the role of Th17 cells during allo-response driven colitis remains ambiguous due to a series of studies with inconclusive results. Interestingly, we recently identified granulocyte-macrophage colony-stimulating factor (GM-CSF+) T cells to be promoted by interleukin-7 (IL-7) signaling and controlled by the activating protein-1 transcription factor family member basic leucine zipper transcription factor ATF-like (BATF) as critical mediators of intestinal GvHD in mice. Given the dual role of BATF, the contribution of IL-23-mediated signaling within donor T cells and bona fide Th17 cells remains to be delineated from the regulation of GM-CSF+ T cells in the absence of BATF. Here, we found in a complete MHC class I-mismatched model that genetic inactivation of the IL-23 receptor (IL-23R) or the transcription factor retinoic acid-related orphan receptor gamma t (RORγt) within donor T cells similarly ablated Th17 cell formation in vivo but preserved the T cells' ability to induce intestinal GvHD in a compared to wild-type controls indistinguishable manner. Importantly, RORγt-independent manifestation of intestinal GvHD was completely dependent on BATF-regulated GM-CSF+ T cells as BATF/RORγt double-deficient T cells failed to induce colitis and the antibody-mediated blockage of IL-7/IL-7R interaction and GM-CSF significantly diminished signs of intestinal GvHD elicited by RORγt-deficient donor T cells. Finally, in analogy to our murine studies, colonic RORC expression levels inversely correlated with the presence of GvHD in allo-HSCT patients. Together, this study provides a crucial example of a BATF-dependent, however, IL-23R signaling- and RORγt-, i.e., Th17 fate-independent regulation of a colitogenic T cell population critically impacting the current understanding of intestinal GvHD.
EVALuna2:34273

Th17 Cell-Mediated Colitis Is Positively Regulated by Interferon Regulatory Factor 4 in a T Cell-Extrinsic Manner - Buchele, Vera; Konein, Patrick; Vogler, Tina; Kunert, Timo; Enderle, Karin; Khan, Hanif; Büttner-Herold, Maike; Lehmann, Christian; Amon, Lukas; Wirtz, Stefan; Dudziak, Diana; Neurath, Markus; et al. (Frontiers in Immunology, 2021)
Inflammatory bowel diseases (IBDs) are characterized by chronic, inflammatory gastrointestinal lesions and often require life-long treatment with immunosuppressants and repetitive surgical interventions. Despite progress in respect to the characterization of molecular mechanisms e.g. exerted by TNF-alpha, currently clinically approved therapeutics fail to provide long-term disease control for most patients. The transcription factor interferon regulatory factor 4 (IRF4) has been shown to play important developmental as well as functional roles within multiple immune cells. In the context of colitis, a T cell-intrinsic role of IRF4 in driving immune-mediated gut pathology is established. Here, we conversely addressed the impact of IRF4 inactivation in non-T cells on T cell driven colitis in vivo. Employing the CD4+CD25− naïve T cell transfer model, we found that T cells fail to elicit colitis in IRF4-deficient compared to IRF4-proficient Rag1−/− mice. Reduced colitis activity in the absence of IRF4 was accompanied by hampered T cell expansion both within the mesenteric lymph node (MLN) and colonic lamina propria (cLP). Furthermore, the influx of various myeloids, presumably inflammation-promoting cells was abrogated overall leading to a less disrupted intestinal barrier. Mechanistically, gene profiling experiments revealed a Th17 response dominated molecular expression signature in colon tissues of IRF4-proficient, colitic Rag1−/− but not in colitis-protected Rag1−/−Irf4−/− mice. Colitis mitigation in Rag1−/−Irf4−/− T cell recipients resulted in reduced frequencies and absolute numbers of IL-17a-producing T cell subsets in MLN and cLP possibly due to a regulation of conventional dendritic cell subset 2 (cDC2) known to impact Th17 differentiation. Together, extending the T cell-intrinsic role for IRF4 in the context of Th17 cell driven colitis, the provided data demonstrate a Th17-inducing and thereby colitis-promoting role of IRF4 through a T cell-extrinsic mechanism highlighting IRF4 as a putative molecular master switch among transcriptional regulators driving immune-mediated intestinal inflammation through both T cell-intrinsic and T cell-extrinsic mechanisms. Future studies need to further dissect IRF4 controlled pathways within distinct IRF4-expressing myeloid cell types, especially cDC2s, to elucidate the precise mechanisms accounting for hampered Th17 formation and, according to our data, the predominant mechanism of colitis protection in Rag1−/−Irf4−/− T cell receiving mice.
CRIS-Team Scopus Importer:2021-02-26
Keywords: inflammatory bowel disease (IBD); interferon regulatory factor 4 (IRF4); intestinal inflammation; myeloid cells; Th17

Thrombocyte apheresis cassettes as a novel source of viable peripheral blood mononuclear cells - Cunningham, Sarah; Buchele, Vera; Brox, Regine; Strasser, Erwin; Hackstein, Holger (Transfusion, 2020)
BACKGROUND: Traditionally, white blood cells (WBCs) are collected from buffy coats or freshly drawn blood. However, the increasing demand for peripheral blood mononuclear cells (PBMCs) in the research phases of immunological therapy development makes it necessary to identify alternative sources of these cells. STUDY DESIGN AND METHODS: Leukapheresis products are cost intensive and not offered by all blood banks. Therefore, thrombocyte apheresis cassettes (TACs), plateletpheresis waste products, were investigated as a possible low-cost and easily accessible blood source for research laboratories. The recovery rate, phenotype, and functionality of WBC subsets from TAC are unknown and were investigated in comparison to frequently used blood resources via flow cytometry. RESULTS: On average, TACs provide 30.3 × 106/mL PBMCs, situating themselves between peripheral whole blood (WB; 5.35 × 106/mL) and leukoreduction system chamber (LRSC; 163.9 × 106/mL) yields. Frequencies of CD14, CD3, CD4, CD8, CD56, CD19, and CD11c positive cells in TACs correlate with normal proportions of WBC populations. Stimulation of TAC-derived PBMCs by lipopolysaccharide (LPS) and resiquimod (R848) showed no significant differences in expression levels of human leukocyte antigen (HLA)-DR, DQ, DP, and CD86 or cytokine secretion compared to other blood source derived PBMC. Following stimulation with LPS or R848, comparable levels of tumor necrosis factor-α, interleukin-10, and interleukin-1β could be measured between TAC, LRSC, and WB. Additionally, TAC-derived T cells retained their proliferation capability and were able to produce interferon-γ following T-cell receptor stimulation. CONCLUSION: TACs provide a cost-effective source of viable and functional human blood cells that can readily be used for clinical and laboratory investigations after plateletpheresis preparation.
CRIS-Team Scopus Importer:2020-03-27